Advances in the Treatment of Desseminated Mycobacterium avium Complex in Adults with AIDS - Carol A Kemper (Canadian Journal of Infectious Diseases)
Although the prospects for successful treatment of Mycobacterium avium complex (MAC) infection in AIDS recently seemed quite dismal, the introduction of the semisynthetic macrolides, clarithromycin and azithromycin, has altered this perspective. Several recent clinical studies have been key to our understanding of the successful management of these patients and are the basis of this review. Yet, some patients with disseminated MAC remain poorly responsive to therapy, intolerance often limits therapy, and recrudescent bacteremia often occurs. Though our understanding of this infection has been rapidly advanced in the past three years. much remains to be learned about its optimal therapeutic management.